Even a mild anemia is related to tumor aggressiveness mediated by angiogenic factors - Krzystek-Korpacka, M.; Matusiewicz, M.; Diakowska, D.; Grabowski, K.; Blachut, K.; KustrzebaWojcicka, I.; Gamian, A. (Experimental Oncology, 2009)
Esophagogastric cancers have high recurrence rates with lymph nodes being a common pattern. Pre-treatment anemia has been
reported an independent prognostic factor of treatment failure regardless of treatment strategy, particularly associated with poor
locoregional control. A causative relationship between anemia — tumor hypoxia — tumor aggressiveness mediated by angiogenesis
up-regulation is advocated, yet remains controversial. Aim: To determine whether and how the pre-treatment anemia is associated
with various aspects of disease aggressiveness and to evaluate the possible involvement of angiogenesis mediators. Methods:
In 111 esophagogastric cancer patients we investigated the association of pre-treatment hemoglobin concentration and anemia
presence with cancer-related, patients-related features and laboratory parameters including angiogenic factors: vascular endothelial
growth factors A and C, interleukin-8 and midkine. Serum levels of angiogenic factors were assessed with immunoenzymatic tests.
Results: Histology, disease stage, regional metastasis and dissemination in general, malnutrition and angiogenesis represented
by midkine were found to correlate with anemia presence and hemoglobin concentration, while tumor extension, patient’s age and
sex accounted only for anemia presence. A tendency towards hemoglobin correlation with VEGF-A and Il-8 was also observed.
Midkine, tumor histology and malnutrition were found to exert an independent effect on pre-treatment hemoglobin concentration
and anemia presence in esophagogastric cancer patients. Hemoglobin level of 12 g/dL was found an optimal cut-off value for discrimination
between localized and disseminated cancers. Conclusions: Even a mild pre-treatment anemia is associated with cancers
metastasizing especially to regional lymph nodes, which seems to be mediated by some of studied angiogenic factors.